Spiraling motion of an underwater glider: Dynamic modeling - Javaid, M.Y. (Asian Research Publishing Network, 2016)
An underwater glider is a class of autonomous underwater vehicles. While these gliders typically move in a saw-tooth pattern, a spiral motion, which may more effective for specific applications, is considered here. The spiral motion of glider may extend its possible applications such as delivery or recovery equipment for subsea installation. In this paper, a spiral glide path for the glider is considered, and the corresponding dynamic model based on Lagrangian principle and analytical expressions determined. The steady-state spiraling equations were derived and solved recursively using the solve algorithm. The results compare well with simulation results based on Newton's method. The spiraling motion is highly maneuverable, with less than 1 m turning radius. Â© 2006-2016 Asian Research Publishing Network (ARPN).